Séries literárias juvenis: autoria e circulação da cultura - Andréa Borges Leão (Ciências Sociais Unisinos)
Observing the phenomenon of cultural movement since the onset of Brazilian publishing industry, the essay offers some ideas on the status of authorship in contemporary series books for young adults. It studies the case of the writer Paula Pimenta. The hypothesis put forward is that the literary authorship regime established far from critical mediation spaces, with no granted awards and seals for school use, changes the national paradigm for the transnational. It starts by commenting on the engagement and recognition of large communities of readers organized on social networks. New issues emerge in the creation process, plot and narrative structure of the novels, as well as regarding the autonomy of the readers in choosing illegitimately their book and in following, for years, far from the school system, the adventures of recurring heroes. What is at stake here is the psychogenesis of learning.